MODIFIED NATURAL ZEOLITE AND BENTONITE AS ADSORBENTS OF HEAVY METAL IONS FROM POLLUTED GROUNDWATER IN YOGYAKARTA URBAN ARE, INDONESIA - Bunchoeun Pich; I Wayan Warmada; Heru Hendrayana; Tetsuro Yoneda (Journal of Applied Geology, 2015)
Groundwater quality in Yogyakarta city has become the major concern due to the presence of heavy metals originated from batik home industries, slaughterhouses, and leather factories, especially in shallow groundwater. In response to the above problems, the naturally abundant zeolite and bentonite in Sidomulyo and Bandung areas were respectively sampled along with the metal-containing groundwater in Yogyakarta urban area for batch adsorption experiment. Before put into experiment, the zeolite and bentonite were characteristically investigated by means of XRD, SEM, chemical composition, and physical property analyses. Also, they were thermally activated to improve their qualities in terms of increase in CEC, whereas the groundwater was analyzed for heavy metal concentrations (Cd, Cr, Cu, Fe, Zn) and its physical property. Five logarithmic amounts of this modified zeolite or bentonite were separately and incrementally introduced into the same three solutions of heavy metals. After the experiment, all the solutions were re-analyzed for the rest of heavy metals to figure out the optimum adsorption capacity of zeolite and bentonite. The outcomes of this experiment will be beneficial in enhancing the groundwater quality for consumptions in Yogyakarta city as well as other places in Indonesia, and will also imply the zeolite and bentonite in commercialization. Keywords: zeolite, bentonite, groundwater, heavy metal, adsorption